1989
DOI: 10.1080/00288233.1989.10423462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sulphur status of East Coast pastures of the North Island, New Zealand 2. Field trials

Abstract: Significant yield responses to spring application of sulphur (S) as a mixture of gypsum and elemental S were recorded at three of five trials conducted in the East Coast region of the North Island. The S-responsive sites included one where there had been no recent application of superphosphate and two which had received regular autumn applications of 25-33 kg S/ha per year as superphosphate. These spring S responses suggest that substantial amounts of sulphate from superphosphate applied in the autumn can be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The lack of response at the other sites studied may have been due to the predominance of low fertility-demanding browntop and little S-responsive clover in the swards. Results from the other trial series (Nguyen et al 1989) showed increased pasture production in response to S at three of the five sites studied despite lower or equal annual rainfall and higher soil sulphate-S levels than in the other trial series. For the two of the three S-responsive sites, it appeared that insufficient of the sulphate-S applied in the previous summer/autumn was retained until the next spring while the other responsive site had no S Table 2 Pasture production responses to S from small plot mowing trials.…”
Section: Sulphurmentioning
confidence: 63%
“…The lack of response at the other sites studied may have been due to the predominance of low fertility-demanding browntop and little S-responsive clover in the swards. Results from the other trial series (Nguyen et al 1989) showed increased pasture production in response to S at three of the five sites studied despite lower or equal annual rainfall and higher soil sulphate-S levels than in the other trial series. For the two of the three S-responsive sites, it appeared that insufficient of the sulphate-S applied in the previous summer/autumn was retained until the next spring while the other responsive site had no S Table 2 Pasture production responses to S from small plot mowing trials.…”
Section: Sulphurmentioning
confidence: 63%
“…Such high urinary S recovery in pasture herbage is surprising since urinary S recovery in pasture herbage with a range of soil S status (Kennedy & Till 1981;Nguyen 1990;Sakadevan 1991;Nguyen & Goh 1993b;Sakadevan et al 1993) was less than 25% over a I-year period. The only other evidence of high urinary S recovery in plants (20-45% recovery after 12 days of urinary application) was that reported by Boswell (1983) in a growth cabinet experiment, where leaching of nutrients such as Nand S from applied urine was absent and ryegrass plants with a stronger ability to take up S than clover plants (Nguyen et al 1989b) were used.…”
Section: Subsoil Sulphurmentioning
confidence: 94%
“…Sulphur fertiliser forms, rates, time of application, and the presence of grazing animals have also been shown to affect the extent of S04 2 -leaching losses from S fertilisers and hence their recycling in the system (e.g., Nguyen et al 1989b;Nguyen 1990;Heng 1991;Heng et al 1991). For example, estimated annual leaching losses from SOi-and elemental S fertilisers applied (50 kg S/ha per year) to pastures that were intermittently grazed by sheep, were 26% (i.e., 13 kg S/ha per year) and 6% (i.e., 3 kg S/ha per year) respectively (Heng et al 1991).…”
Section: Sulphate Leaching Losses From Fertilisersmentioning
confidence: 99%
“…Las pérdidas por lixiviación como SO 4 -2 son más altas en suelos más livianos, comparados con suelos con mayor contenido de arcilla, debido a una menor capacidad de retención del SO 4 -2 y a una mayor velocidad de penetración del agua en el perfil del suelo (Scherer, 2001). La lixiviación del S puede ser tan importante durante los meses de invierno, que incluso podrían estar limitando el crecimiento de las plantas en la primavera siguiente, aún cuando se hayan realizado fertilizaciones con azufre en el otoño anterior (Nguyen et al, 1989 (1986) citado por Morón (1996), en regiones con altos niveles de industrialización, estas entradas de S pueden llegar a los 200 kg S/ ha/año, mientras que en áreas rurales fuera de la influencia industrial los valores son de 5 kg S/ha/año.…”
Section: Azufre En Los Suelosunclassified